Management and Outcome of Diabetic Foot-A Study of Hundred Case (Journal of Surgical Sciences, 2020)
Background: Diabetes mellitus is a complex metabolic disorder that affect 1-2 percent of the population. It can give rise to many tissue complications among which foot is particularly vulnerable to circulatory and neurological disorder, so that even minor trauma can lead to ulceration and infection.Methods: Between September 2008 and August 2009, 100 patients were undergone treatment for diabetic foot at department of Surgery, Shaheed Ziaur Rahman Medical College Hospital, Bogra. This study included all the cases of diabetic foot irrespective of age, sex and diabetic status.Results: After 12 weeks treatment 84% of patient were completely recovered, 2% developed abscess, 8% developed ulceration and 6% developed gangrene. Mean age of diabetic patients with foot ulcer is 50-60 years. Out of 100 cases 64% male and 36% female. Maximum number of patient (64%) had foot problems after suffering from diabetes mellitus for a period of 6-10 years.Conclusion: The modalities of treatment of diabetic foot should be selected for each type of pathology depending on the pattern of presentations of diabetic foot. Careful selection of treatment modalities can reduce the rate of diabetic foot complications and improve the quality of life of diabetic patients.Journal of Surgical Sciences (2019) Vol. 23 (1) : 25-28